2023
DOI: 10.1136/bmjopen-2022-067223
|View full text |Cite
|
Sign up to set email alerts
|

How do the older adults in nursing homes live with dignity? A protocol for a meta-synthesis of qualitative research

Abstract: IntroductionAs the population continuous to age and family sizes decrease, residing in nursing homes has emerged as a crucial option for older adults’ care. Ensuring a dignified life for older adults in nursing homes is critical for enhancing their overall quality of life. The primary objective of this study is to synthesise the evidence of qualitative research on the feelings and experiences of dignity among older adults living in nursing homes. This will enable a better understanding of the factors influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The Chinese nursing assistants are generally older, and their cultural background is low ( 13 ). Furthermore, some of these assistants lack basic courtesy and respect and might be unkind and rude, which damages the dignity of the older adult ( 14 ) and may also affect their trust in the care service. A survey of 1,544 staff across 92 English care home units revealed that very few staff carried out specific person-centered activities ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese nursing assistants are generally older, and their cultural background is low ( 13 ). Furthermore, some of these assistants lack basic courtesy and respect and might be unkind and rude, which damages the dignity of the older adult ( 14 ) and may also affect their trust in the care service. A survey of 1,544 staff across 92 English care home units revealed that very few staff carried out specific person-centered activities ( 15 ).…”
Section: Introductionmentioning
confidence: 99%